2020
DOI: 10.21601/ejbms/9314
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the Identification of Antibiotics Residues in Raw Bovine Milk in Algeria

Abstract: The presence of residues of veterinary drugs such as antibiotics used for the treatment of animals can be dangerous for the consumer. Indeed, residues of these drugs can end up in the form of undesirable traces in animal productions, in particular milk when there is an inappropriate use such as failure to comply with the waiting times between the administration of antibiotics to the animal and meat collection. This study is part of a global project carried out with the aim of evaluating the presence of antibio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Titouche et al (2013) examined the incidence of antibiotic residues in raw milk in the Tizi-Ouzou area and found that 46.78% of 171 screened samples were positive. In Blida, Ouabdesselam et al (2020) showed that 20.51% of 200 milk samples were positive for antibiotic residues. Their presence indicates a poor utilization especially the non-abidance of the withholding period (Abiola et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Titouche et al (2013) examined the incidence of antibiotic residues in raw milk in the Tizi-Ouzou area and found that 46.78% of 171 screened samples were positive. In Blida, Ouabdesselam et al (2020) showed that 20.51% of 200 milk samples were positive for antibiotic residues. Their presence indicates a poor utilization especially the non-abidance of the withholding period (Abiola et al, 2005).…”
Section: Introductionmentioning
confidence: 99%